Unfinished business : the politics of 'dissident' Irish republicanism - McGlinchey, Marisa (Manchester Political Studies, 2019)
'This book describes and assesses the politics of 'dissident' Irish republicanism. It offers an analysis of who the 'dissidents' are and what they hope to achieve. Moving beyond simplistic stereotypes it explores the range of ideological and organisational strands which exist throughout the movement and explains why we have not witnessed the development of a formal unified structure between groups and independents. The work examines issues of legitimacy and mandate and provides an in-depth assessment of where 'dissidents' derive their mandate. Historical continuity operates alongside contemporary circumstances. To focus on electoral mandates fails to acknowledge the core of republican ideology which stresses a line of historical continuity drawn from 1798 and 1916, leading 'dissidents' to largely reject the label 'dissident'. This book draws upon unprecedented access to ninety 'dissident' republicans throughout Ireland. Interviewees include independent republicans, elected representatives, political groups and societies, militant organisations, current prisoners in Maghaberry prison and a number of 'the hooded-men'. Uniquely, the book also includes former members of the Provisional IRA who held senior positions prior to their departure from that movement. Written amidst academic and public controversy this book is the first to provide such a holistic assessment of 'dissident' republicanism. It is the largest collection of 'dissident' testimonies to date uniquely providing a wide geographical and generational record of this radical republican current.'Dissident' republicanism continues to elicit strong opinions throughout Ireland and beyond. This book is a land mark study of 'dissident' republicanism and will significantly shape our understanding of 'dissidents' for years to come' --Back cover.